Congenital fibrosarcoma of the knee. Case report - Páez, Jorge Eduardo; Quintero-Ariza, Alvaro (Revista Colombiana de Ortopedia y Traumatología, 2020)
Congenital fibrosarcoma is an unusual pathology, representing 3% of all childhood tumors. The purpose of the publication is to describe the clinical case of a patient with a congenital fibrosarcoma, successfully treated surgically without recurrences with good functional results. We describe the clinical outcome of a 3-month-old of age with a mass in the left thigh by a congenital fibrosarcoma 10 cm, who underwent primary resection of the lesion with edges free of tumor compromise as the treatment of choice. During follow-up, the patient did not present relapses with recovery of active and passive mobility arcs, with motor development according to age. The congenital fibrosarcomas, are located mainly around the knee, and are infiltrating to adjacent tissues; management is surgical resection with tumor-free edges. Congenital Fibrosarcoma usually has better prognosis than adults sarcomas, but with recurrence rates up to 40% of the patients. Evidence Level: IV